Spontaneous Iliopsoas Hematoma following Microvascular Free Tissue Transfer - Jeffrey D. Markey; A. Sean Alemi; Margaret L. Naunheim; Daniel L. Faden; Chase M. Heaton; Rahul Seth (Case Reports in Otolaryngology)
Spontaneous hematoma within the iliopsoas muscle (SIH) is a rare complication most commonly seen in coagulopathic patients. Often, patients undergoing microvascular free tissue transfer are anticoagulated for anastomotic patency. Here we describe two cases of postoperative SIH following contralateral anterolateral thigh (ALT) free tissue transfer for reconstruction of oncologic head and neck defects. Both patients described hip pain after mobilization and had a corresponding acute blood loss anemia. Diagnosis of SIH was confirmed by CT and both patients were managed conservatively. Given that anticoagulation is a common practice following head and neck free tissue transfer, surgeons should be aware of this potential complication.